Strategi Pembelajaran Kolaboratif dalam Meningkatkan Hafalan Al-Qur’an Anak: Studi di PKBM Liwaul Hamdi - Miftahurrahmat, Miftahurrahmat; Mashuri, Mashuri; Nurjanah Ismail; Hadi, Abdul (Jurnal Ilmiah Guru Madrasah, 2025)
This study aims to determine the form of cooperation between teachers and parents in improving children's responsibility in memorising the Qur'an at PKBM Liwaul Hamdi. This study uses a descriptive qualitative method with data collection techniques through observation, questionnaires, and interviews. The results of the study indicate that the active roles of teachers and parents are crucial in supporting children in memorising the Qur'an. Positive attitudes, exemplary behaviour, and integrity on the part of teachers and parents are key factors in fostering children's sense of responsibility towards their memorisation. Additionally, intensive communication and the ability to manage emotions in supervising children constitute effective forms of collaboration. This study emphasises that collaboration between teachers and parents not only impacts children's memorisation success but also shapes their character and religious attitudes. Therefore, this synergistic relationship needs to be consistently nurtured in various educational institutions as part of a character education strategy based on Islamic values.